Pengaruh Konfigurasi Habitat Lahan Basah Terhadap Kelimpahan Burung Air Wilayah Mangrove Cemtre Dan Sekitarnya di Kecamatan Jenu, Kabupaten Tuban - Subiyanto, Subiyanto (Jurnal Matematika dan Ilmu Pengetahuan Alam, 2015)
The influence of the environment and the presence of waterbird is analyzed in individual abundance of watebird in the wetland which consists of estuaries, mangroves, beaches, ponds, and rivers around the Mangrove Centre, District of Jenu Tuban. The study can provide information about the habitat elements which is considered as components of wetland habitat configurations which has a capacity of prediction of the emergence of water birds. Habitat configuration which includes elements of the habitat that consists of land area, extensive vegetation cover and salinity, is the independent variable that is expected to predict the emergence of water bird. Data collection was carried out directly in the observation stations and implemented in the laboratory. Samples of data were obtained from seven observation stations in the wetland complex that includes the estuary area, mangrove, beach-1, beach-2, pond-1, pond-2, and rivers. For wide area and vegetation cover were observed directly (in situ) while the salinity was analyzed in the laboratory (ex situ). Pearson Product Momment Correlation used for simple correlation analysis on the variables, and Standard Multiple Regression is used to examine the characteristics of the wetland habitat as the independent variable and the abundance of individuals of each species as the dependent variable, for each period in the rainy season and dry season. The results suggest a link between the configuration of wetland habitat with an abundance of water birds, especially extensive vegetation cover greatly affect the abundance of water birds. So it is recommended to conduct a conservation in a number of wetland, with extensive attention to the addition of vegetation around the open water in the wetland complex in order to maintain the abundance of species of water birds.Keywords: wetlands, habitat configuration, abundance, waterbirds, conservation.